Feasibility of Cognitive Functions Screened With the Montreal Cognitive Assessment in Determining ADL Dependence Early After Stroke - Abzhandadze, Tamar; Rafsten, Lena; Lundgren-Nilsson, Åsa; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2018)
Objective: To investigate the feasibility of assessing cognitive function using the Montreal Cognitive Assessment (MoCA) given 36–48 h post stroke to explain dependence in activities of daily living (ADL). Methods: This is a cross-sectional, exploratory study. Cognitive function and basic ADL were assessed with the MoCA and the Barthel Index (BI), respectively, within 36–48 h of admission. Neurological functions were assessed with the National Institute of Health Stroke Scale (NIHSS) upon admittance to the hospital. Binary logistic regression analyses were performed to assess the feasibility of the MoCA in explaining ADL dependence. Results: Data were available for 550 patients (42% females, mean age 69 years). Moderate correlations (rs > +0.30, p < 0.001) were found between the total score on the BI, MoCA, and visuospatial/executive functions. The regression analysis model including only MoCA as an independent variable had a high sensitivity for explaining ADL dependence. However, the model with independent variables of MoCA, NIHSS, and age had the best area under the curve value (0.74). Conclusions: Cognitive functions assessed with the MoCA partly explain ADL dependence 36–48 h post stroke. Stroke-related neurological deficits and age should be additional considerations.